IMRT point dose measurements with a diamond detector - Barnett, Erin (Radiology and oncology (Ljubljana), 2005)
Background. Radiation dose distribution calculations used in treatment planning systems (TPS) describe dose deposition well for large fields. For small fields encountered in Intensity Modulated Radiation Therapy (IMRT) thesemodels may be less accurate. Dose verification of IMRT fields is therefore essential in IMRT implementation and quality assurance. For these smaller fields, lateral electronic eguilibrium may not exist and volume averaging effects in ion chambers become increasingly problematic. For this reason, detectors with sensitive volumes smaller than that of conventional ionchambers are preferable in both small fields and high dose gradient region.Diamond detectors are capable of making such accurate dosimetric measurements. Methods. This study compares dosimetry measurements made with a PTW-Freiburg type 60003 diamond detector, an Exradin A12 ion chamber, a PTW-Freiburg PinPoint ion chamber and a Varian aS500 EPID. Dose measurements were made in a clinical prostate intensity modulated beam. Due to difficultiesencountered when dosimetric measurements are made in high dose gradient regions, probe positioning within IMRT fields was investigated and a method to establish better probe positions is proposed. Measured doses were compared with HELAX-TMS calculated doses to verify performance of the TPS usedin this center. Results. The diamond detector dosimetry is extremely sensitive to positioning particularly in high dose gradient regions. The results indicate that improved agreement between doses measured with various dosimeters can be obtained by appropriate selection of the probe position. Avoidance of high dose gradient regions improves agreement between measured doses particularly for the PinPoint chamber, the diamond detector and the EPID. Conclusions. The use of diamond detectors and EPIDs in dosimetry is an attractive option particularly for verification of IMRT treatments. (Abstract truncated at 2000 characters).
Keywords: obsevanje; Prostata, novotvorbe; Prostatic Neoplasms; Radioterapija; Radioterapija, doziranje; Radiotherapy; Radiotherapy Dosage; therapy; zdravljenje